2016
DOI: 10.1017/cem.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

MP023: Reasons for referral and hospitalization among emergency department patients with syncope

Abstract: Introduction: Syncope can be caused by serious life-threatening conditions not obvious during the initial ED assessment leading to wide variations in management. We aimed to identify the reasons for consultations and hospitalizations, outcomes, and the potential cost savings if an outpatient cardiac monitoring strategy were developed. Methods: We conducted a prospective cohort study of adult syncope patients at 5 academic EDs over 41 months. We collected baseline characteristics, reasons for consultation and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A prospective cohort study of 4064 patients from 5 emergency units demonstrated that cardiac arrhythmia syncope is the leading cause of hospitalization in adult patients with syncope, reaching 84.2% of 165 hospitalized patients. Furthermore, arrhythmia was the most common serious adverse event after discharge directly from the emergency unit or hospital [15]. Among the arrhythmias, the correlation between the syncope symptom and VT record, supraventricular tachycardia (with heart rate ≥ 160 bpm) or asystole ≥ 3 s is considered a gold standard for diagnosis [1].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study of 4064 patients from 5 emergency units demonstrated that cardiac arrhythmia syncope is the leading cause of hospitalization in adult patients with syncope, reaching 84.2% of 165 hospitalized patients. Furthermore, arrhythmia was the most common serious adverse event after discharge directly from the emergency unit or hospital [15]. Among the arrhythmias, the correlation between the syncope symptom and VT record, supraventricular tachycardia (with heart rate ≥ 160 bpm) or asystole ≥ 3 s is considered a gold standard for diagnosis [1].…”
Section: Discussionmentioning
confidence: 99%